2017
DOI: 10.1159/000478789
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radical Prostatectomy and Radiotherapy in Treatment of Locally Advanced Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: The role of radical prostatectomy (RP) is still controversial for locally advanced prostate cancer (PC). Radiotherapy (RT) and hormonal therapy (HT) are usually used as a primary treatment. Material and Methods: A systematic online search was conducted according to Preferred Reporting Items for Systematic Review and Meta-Analysis statement. Eligible publications reporting the overall survival (OS) and/or disease-specific survival (DSS) were included. A total of 14 studies, including 17,869 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
6
22
0
1
Order By: Relevance
“…Indeed, patients elected to RP should be sharply informed about the risk of unfavorable pathologic findings such as multifocal PSMs, which associate with cancer invading the capsule or seminal vesicles. These patients should be informed about the increased probability of radiotherapy and androgen deprivation therapy or radiotherapy alone if androgen deprivation therapy is contraindicated [6,14,28,29]. Our model gives a tool to evaluate the risk of PSMs according to preoperative TT levels as well as to the D'Amico clinical risk classes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients elected to RP should be sharply informed about the risk of unfavorable pathologic findings such as multifocal PSMs, which associate with cancer invading the capsule or seminal vesicles. These patients should be informed about the increased probability of radiotherapy and androgen deprivation therapy or radiotherapy alone if androgen deprivation therapy is contraindicated [6,14,28,29]. Our model gives a tool to evaluate the risk of PSMs according to preoperative TT levels as well as to the D'Amico clinical risk classes.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve-sparing surgery is generally restricted to patients with organ-confined disease. Extension of PCa outside the prostatic capsule requires dissection of the neurovascular bundle, for nerve-sparing surgery would increase the risk of positive surgical margins [ 3 , 4 , 6 ]. The assessment of the local tumor stage is similarly important when radiotherapy is chosen as treatment and guides decisions on radiation dose, radiation template, and adjuvant therapies [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a systematic review of adjuvant HT plus NHT with RP or RT for high risk or locally advanced PC revealed that NHT before RP did not significantly improve OS (odds ratio, 1.11; p=0.69). 27 Nevertheless, it did provide significant im- In our study, the RT group showed better 5-year OS rate than the RP group. The authors presume that the reason for this is due to the fact that the number of RP group was higher and the FU duration was longer than RT group.…”
Section: Discussionmentioning
confidence: 53%